(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
In MANET mobile nodes are communicating through wireless medium and do not require any pre-existent infrastructure. In MANET all mobile nodes behaves as router and when required they takes part in discovery and maintenance of the route to the other node. Without the fixed base station the mobile nodes dynamically exchange data among themselves. Popularity of MANET has been increased because of the availability of license-free wireless communication devices. MANET can be used for disaster-management, business meetings, military operations, rescue operations, or in a situation, where temporary communication network among some nodes is demanded. ZRP is a well known hybrid routing protocol. To understand its suitability we must understand its behavior under various real time conditions. This paper presents performance analysis of AODV routing protocol over OLSR and ZRP routing protocols using QualNet version 6.1. This experiment uses different network conditions, close to real time condition, for the performance analysis of AODV using OLSR and ZRP as a reference protocol. Simulations are carried out to analyze the different network parameters such as throughput, average jitter, average end-to-end delay and packet delivery ratio.